Faktor yang Berhubungan dengan Kejadian Anemia pada Ibu Hamil Trimester III - Anjelina Puspita Sari; Romlah Romlah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the factors associated with the incidence of anemia in third trimester pregnant women. The research design of this research is a cross sectional study. The results of this study showed that there was no significant relationship between age and anemia in third trimester pregnant women (p = 0.23). The results of this study indicated that there was a significant relationship between gravida and the incidence of anemia in third trimester pregnant women (p = 0.041). The results of this study also showed a significant relationship between pregnancy and the incidence of anemia in third trimester pregnant women (p = 0.04). The results of this study showed that there was no significant relationship between the frequency of ANC and the incidence of anemia in third trimester pregnant women (p = 0.30). In conclusion, this is a significant relationship between pregnancy and pregnancy interval with the incidence of anemia in third trimester pregnant women. There is no significant relationship between age and frequency of ANC with the incidence of anemia in third trimester pregnant women. Keywords: Anemia Factors, Three Trimester Pregnant Women